Pengembangan Model Training of trainer pada Pelajaran Tematik untuk Anak Inklusi - Dedy Putranto; Fandi Nugroho (Jurnal Muara Olahraga, 2018)
This study aims to: (1) develop TOT learning module for inclusive elementary schozols and (2) find out the feasibility of the learning module for developed inclusive elementary schools. The trial of this research subject was the sports teacher of SD N 33 Pangkalpinang. The research is carried out using a research and development model which included several stages: (1) planning; (2) design; (3) product development and (4) evaluation. The planning stage includes initial preparation. The design phase includes the preparation of the program structure, the making of story boards, the design of interfaces, the preparation of the systematic presentation of material, illustrations, visualization. The product development stage consists of writing text, installing an evaluation model development image. The evaluation phase is carried out in the form of an alpha test in the form of expert material validation, and beta test by elementary school teachers. The result of the study produce a learning module that is in accordance with its function. The result of the average rating in the percentage of validators by material experts is 82.5% with the category "Very Good". The feasibily of develop TOT learning module for inclusive children with the score obtained of 82,5% and the average score is 4,125 with the category of very good, view aspect evaluation is 41 and the average is of 4,1 with very good category. Content aspect is of 41,5 with very good category. To conclude the learning module is worth using.